Peningkatan Kesadaran Masyarakat terhadap Keselamatan Listrik demi Kesehatan dan Kesejahteraan Rumah Tangga - Yulius Evan Christian; Hamdan Mustopa; Dini Permata Sari; Putriana Rachmawati; Sharon Susanto (UNIVERSITAS 17 AGUSTUS 1945 JAKARTA, 2026)
Leakage of electrical current is one of the leading causes of electrical accidents and household fires, particularly due to unsafe installations. Low awareness of this hazard, along with limited understanding of safety devices such as Earth Leakage Circuit Breakers (ELCB), prompted the implementation of a community service program in RW 04, Kalibaru Subdistrict, North Jakarta. Educational outreach, interactive discussions, and simulations of ELCB installation using a participatory educational approach were conducted through pre- and post-tests involving 34 participants. The results showed an increase in the average score from 40.30% in the pretest to 100% in the post-test. All indicators showed improvement, particularly in terms of understanding the PUIL, ELCB functions, emergency response to electric shock, and the importance of certified technicians. Statistical analysis revealed a significance value of p < 0.05, indicating a significant difference before and after the program. This activity has proven empirically effective in increasing community literacy on electrical safety and is recommended for replication in other areas with similar conditions.